PKM Literasi AI: Pelatihan Penggunaan Gemini Sebagai Media Presentasi Interaktif Mahasiswa Pendidikan Guru Sekolah Dasar - Marzuki, Andika; Nursalim; Syarifuddin; Muhammad Ikhsan Sukaria; Muhammad Awal Nur (Jurnal Abdi Masyarakat Pendidikan, 2025)
The rapid development of Artificial Intelligence (AI) requires prospective primary school teachers to possess adequate AI literacy and scientific communication skills, particularly in presenting research proposals in an engaging and well-argued manner. Preliminary observations of sixth-semester PGSD (Primary School Teacher Education) students at Bone indicated that 72% experienced difficulties in structuring and delivering their proposals, as reflected in incoherent presentation flow, less communicative visuals, and limited use of digital presentation technologies. This community service program aimed to enhance students’ AI literacy and scientific presentation skills through training on the use of Canvas Gemini as an interactive medium for research proposal presentations. The program employed a participatory–educative approach through stages of socialization, technical training, mentoring, and evaluation, involving 30 PGSD Bone students. Data were collected through observation, a 15-item multiple-choice pretest–posttest, assessment of interactive slide products, and a participant response questionnaire. The results showed an increase in the average score of understanding and skills from 56.4 (pretest) to 88.2 (posttest). Approximately 80% of participants succeeded in producing at least one interactive slide representing the research problem or conceptual framework more coherently, while 94% stated that the training was relevant to their academic needs and 89% expressed interest in using Canvas Gemini for future presentations.